Place of M-cholinolytics in the medical and diagnostic technology of handling women with urinary incontinence - V V Danilov; I Yu Volnikh; S A Luchinskii; V V Danilov; E V Eliseeva (IP Berlin A.V., 2014)
We observed a group of patients (81 women of mean age around 55 years) with stress urinary incontinence, who, after surveying and preparatory conservative treatment underwent the trocar synthetic sling surgery. Postoperatively, in 24% of patients an overactive bladder syndrome was recorded, and therefore the therapeutic appointment of M-cholinolytic trospium chloride (Spazmeks) was made. As a result, the micturition disorders were corrected. According to the neurophysiological model, the prescription of M-cholinolytics for a long period is quite reasonable and safe in the absence of bladder outlet obstruction.